Herpes simplex virus: isolation, cytopathological characterization and antiviral sensitivity - Carlos Nozawa; Lilian Yumi Hattori; Ligia Carla Faccin Galhardi; Nayara Lopes; Wesley Andrade Bomfim; Ligyana Korki de Cândido; Elbens Marcos Minoreli de Azevedo; Airton dos Santos Gon; Rosa Elisa Carvalho Linhares (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND:Herpes simplex virus (HSV) infection is an endemic disease and it is estimated that 6095% of the adult population are infected with symptoms that are usually self-limiting, though they can be serious, extensive and prolonged in immunocompromised individuals, highlighted by the emergence of drug-resistant strains. The study of the wild-type HSV strains based on the cytopathogenic features and its antiviral sensitivity are important in the establishment of an antivirogram for controlling the infection.OBJECTIVE:This study sought to isolate and examine the cytopathological characteristics of circulating strains of the Herpes simplex virus, from clinical specimens and their sensitivity to commercially available antiherpesvirus drugs, acyclovir, phosphonophormic acid and trifluridine.METHODS:Herpes simplex virus isolation, cytopathological features and antiviral sensitivity assays were performed in cell culture by tissue culture infectious dose or plaque forming unit assay.RESULTS:From twenty-two clinical specimens, we isolated and adapted nine strains. Overall, the cytopathic effect was detected 24 h post-infection (p.i.) and the presence of syncytia was remarkable 48 h p.i., observed after cell staining. Out of eight isolates, four developed plaques of varying sizes. All the isolates were sensitive to acyclovir, phosphonophormic and trifluridine, with the percentage of virus inhibition (%VI) ranging from 49.7-100%.CONCLUSIONS:The methodology for HSV isolation and characterization is a straightforward approach, but the drug sensitivity test, regarded as being of great practical importance, needs to be better understood.